LEXICAL TERMINOLOGY IN TEACHING FOREIGN LANGUAGES - Atadjanova Rokhat Butanbaevna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, thoughts and observations on teaching foreign languages, particularly regarding lexical terminology, are discussed. Language is a powerful tool that connects individuals, cultures, and ideas across the globe. Teaching a foreign language requires a nuanced understanding of its components, and lexical terminology plays a crucial role in shaping language instruction. Lexical terms encompass the building blocks of vocabulary, allowing learners to express thoughts, emotions, and actions effectively. At its core, lexical terminology refers to the vocabulary and word choices that form the linguistic fabric of a language. It goes beyond individual words, encompassing phrases, idioms, and expressions that are integral to effective communication.